Updates in pathobiological aspects of anaplastic large cell lymphoma - Wu, Rui; Lim, Megan S. (Frontiers in Oncology, 2023)
Anaplastic large cell lymphomas (ALCL) encompass several distinct subtypes of mature T-cell neoplasms that are unified by the expression of CD30 and anaplastic cytomorphology. Identification of the cytogenetic abnormality t(2;5)(p23;q35) led to the subclassification of ALCLs into ALK+ ALCL and ALK-ALCL. According to the most recent World Health Organization (WHO) Classification of Haematolymphoid Tumours as well as the International Consensus Classification (ICC) of Mature Lymphoid Neoplasms, ALCLs encompass ALK+ ALCL, ALK-ALCL, and breast implant-associated ALCL (BI-ALCL). Approximately 80% of systemic ALCLs harbor rearrangement of ALK, with NPM1 being the most common partner gene, although many other fusion partner genes have been identified to date. ALK-ALCLs represent a heterogeneous group of lymphomas with distinct clinical, immunophenotypic, and genetic features. A subset harbor recurrent rearrangement of genes, including TYK2, DUSP22, and TP63, with a proportion for which genetic aberrations have yet to be characterized. Although primary cutaneous ALCL (pc-ALCL) is currently classified as a subtype of primary cutaneous T-cell lymphoma, due to the large anaplastic and pleomorphic morphology together with CD30 expression in the malignant cells, this review also discusses the pathobiological features of this disease entity. Genomic and proteomic studies have contributed significant knowledge elucidating novel signaling pathways that are implicated in ALCL pathogenesis and represent candidate targets of therapeutic interventions. This review aims to offer perspectives on recent insights regarding the pathobiological and genetic features of ALCL.